Study of Single Walled Carbon Nanotubes Irradiated by Swift Heavy Ions. (2016) - Vishalli,; Kaur, Ramneek; Raina, K.K.; Avasthi, D.K.; Jeet, Kiran; Srivastava, Alok; Dharamvir, Keya
Abstract: Carbon nanotubes (CNTs) have found applications in various fields such as in radiation shields, field storage devices and as nano-devices in space ships, where these materials may be exposed to severe radiation environment. Thus it is interesting to observe the effect of ion beam irradiation on this system. A study on structural modifications in single walled carbon nanotubes (SWCNTs) under swift heavy ions has been presented. Langmuir Blodgett (LB) technique is used to deposit SWCNT thin film of fairly uniform thickness over the quartz substrate. The surface morphology of deposited film has been studied by using Scanning Electron Microscopy (SEM). The SWCNT thin films have been irradiated with carbon ion beam of energy 60 MeV with fluences ranging from 3x10 11 to 1x10 14 ions/cm 2 . The structural modifications in the LB thin films have been investigated by using Raman spectroscopy before and after irradiation. The decrease in disorder parameter has been observed up to certain values of fluence and it starts to increase for further higher fluences. Thus two processes have been observed-defect creation and defect healing. For the lower fluence values the defect healing is dominant while at higher fluence defect creation dominates.